Analisis Pemanfaatan Faktor Produksi pada Usahatani Padi Sawah di Kabupaten Konawe Sulawesi Tenggara - Rusli, Supriady (Universitas Brawijaya, Indonesia, 2009)
Research aims to find out: the factors that affect the production of rice and farm income of rice in the Regency Konawe, Population in this research is all rice farmers in the research location, determination of the sample in this research is using multistage random sampling method, which is 2 stage, (1) the determination of stages and the sub-district for sample (2), the determination of the sample farmers. The determination of sample districts purposively sampling methods, so that the 3 sub-districts selected as the location of research, namely: Wawotobi district, Lambuya district and Unaaha district. Population of rice farmers in three districts of the 1230 people. The determination of the sample farmers using simple random sampling method and was selected as 130 rice farmers in the research samples. Results of research indicate that: (a) factors of production area, fertilizer urea, SP36 fertilizer, manure and KCl significantly affect the production of rice. While the factors of production of seeds, pesticides and labor does not significantly affect the production of rice, and (b) the use of factors of production area, seed, fertilizer urea, fertilizer SP36, KCl fertilizer, pesticides and labor is relatively not economically efficient. Therefore need to have a new breakthrough for the efficient utilization of input on farmer rice research in the area.